2013
DOI: 10.1016/j.bbmt.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Hematopoietic Cell Transplantation in First Remission Abrogates Poor Outcomes Associated with High-Risk Pediatric Acute Myeloid Leukemia

Abstract: Despite remission rates of approximately 85% for children diagnosed with acute myeloid leukemia (AML), greater than 40% will die from relapsed disease. Patients with poor-risk molecular/cytogenetics and/or inadequate response to upfront therapy are typically considered high-risk (HR) and historically have poor outcomes with chemotherapy alone. We investigated whether allogeneic hematopoietic cell transplantation (allo-HCT) with best available donor in first remission (CR1) would abrogate the poor outcomes asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 33 publications
3
27
1
Order By: Relevance
“…Both chemobased and TBI-based conditioning regimens still remain administered. 12,21 In 1994, Michel et al, published a previous French study comparing two different Bu-based conditioning regimen. 5 In this study, the authors reported better results for patients who received 200 mg/kg as total dose of CY rather than those who received 120 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both chemobased and TBI-based conditioning regimens still remain administered. 12,21 In 1994, Michel et al, published a previous French study comparing two different Bu-based conditioning regimen. 5 In this study, the authors reported better results for patients who received 200 mg/kg as total dose of CY rather than those who received 120 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…However, including those in North America, some groups still continue using TBI-based conditioning regimen. 12,13 Then, we conducted a retrospective study to analyze the impact of conditioning regimen on the longterm OS of children who underwent HSCT for AML in CR1. We report the results regarding patients o18 years who received allogeneic HSCT from either sibling or alternative donor in France from 1980 to 2004 after myeloablative TBI-based conditioning regimen or Bu-based conditioning regimen for AML in CR1.…”
Section: Introductionmentioning
confidence: 99%
“…High-risk acute myeloid leukemia (HR-AML) has not been treated with the same success for favorable or intermediate acute myeloid leukemia [1]. Although the majority of patients with HR-AML achieve complete remission (CR) after intensive induction therapy, most of them will die from Biology of Blood and Marrow Transplantation j o u r n a l h o m e p a g e : w w w .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A 2-year overall survival (OS) of 50-70% is expected with the standard approach to GvHD prevention in recipients of allogeneic grafts if transplanted in CR. [3][4][5] The increased use of unrelated and mismatched family (haploidentical) donors became possible due to improvements in unrelated donor registries, high-resolution HLA-typing and new methods of in vivo and ex vivo graft manipulation. 6,7 The major obstacle to the success of both unrelated and haploidentical transplantation is leukemia relapse.…”
Section: Introductionmentioning
confidence: 99%